Sobre el concepte de derivació fonològica: alguns fenòmens vocàlics en basc i en català - Hualde, José Ignacio (Caplletra. Revista Internacional de Filologia, 1995)
In the standard generative model, phonological rules are strictly ordered, potentially giving rise to complicated derivations with a large number of intermediate representations. In such a model, the order in which the rules apply is as important as the correct formulation of the rules. There are obvious conceptual problems with this theoretical framework, and in recent years several proposals which do away with rule ordering have been put forward. In this paper, we examine a number of vocalic alternations in Basque and Valencian (Southern Catalan), which in a standard generative analysis require a complex rule ordering. Adapting Lakoff' s model we show that, in every case, we can have a simple mapping between two levels with all operations applying simultaneously. In these cases at least, rule order can be shown to be an unnecessary complication.